2018
DOI: 10.31688/abmu.2018.53.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adiposity Index (Vai) – A Potential Marker of Cardiometabolic Risk

Abstract: L'indice d'adiposité viscérale (IAV) -marqueur potentiel du risque cardio-métabolique L'importance du risque cardiovasculaire/cardio-métabolique est particulière car le contrôle de ses composantes peut affecter l'athérogenèse et ses conséquences cliniques: la cardiopathie ischémique, la maladie cérébrovasculaire, l'artériopathie périphérique et le diabète sucré (DS). Pour évaluer le risque cardio-métabolique associé à l'obésité viscérale, on a essayé d'identifier un indicateur utile dans la pratique clinique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
(44 reference statements)
0
13
0
Order By: Relevance
“…The classification of overweight or obesity according to the body mass index (BMI) has been commonly employed, even though other scales, such as waist circumference (WC), waist to height ratio (WtHR), and University of Navarra Clinic-Body Fat Estimator (CUN-BAE) are emerging to be considered as novel indicators in clinical research for the diagnosis of obesity [ 5 ]. Other indicators, such as Equation Córdoba for Estimation of Body Fat (ECORE-BF), relative fat mass (RFM), Palafolls formula, Deurenberg fat mass index, body roundness index (BRI), body shape index (ABSI), visceral adiposity index (VAI) [ 6 ], conicity index, normalized weight-adjusted index (NWAI), body surface index (BSI), body surfaces area (BSA), or body fat index (BFI), are used for stratification into the different categories of overweight and obesity, according to gender differences in body composition.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of overweight or obesity according to the body mass index (BMI) has been commonly employed, even though other scales, such as waist circumference (WC), waist to height ratio (WtHR), and University of Navarra Clinic-Body Fat Estimator (CUN-BAE) are emerging to be considered as novel indicators in clinical research for the diagnosis of obesity [ 5 ]. Other indicators, such as Equation Córdoba for Estimation of Body Fat (ECORE-BF), relative fat mass (RFM), Palafolls formula, Deurenberg fat mass index, body roundness index (BRI), body shape index (ABSI), visceral adiposity index (VAI) [ 6 ], conicity index, normalized weight-adjusted index (NWAI), body surface index (BSI), body surfaces area (BSA), or body fat index (BFI), are used for stratification into the different categories of overweight and obesity, according to gender differences in body composition.…”
Section: Introductionmentioning
confidence: 99%
“…10 VAI is a mathematical formula that consists of laboratory parameters and the core elements of anthropometry such as BMI and WC, TGs, and HDL-C. 11 Sigina et al suggested that VAI can be considered as a potential tool for assessing cardiometabolic risk. 12 There is a significant association of VAI with the different components of metabolic syndrome in older men and women including hyperglycemia, hypertriglyceridemia, low HDL-cholesterol, and abdominal obesity. 13 Previous study revealed that VAI can provide an estimation of subclinical atherosclerosis than the calculation of Homeostatic Model Assessment of Insulin resistance (HOMA-IR) in individuals prone to T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…Visceral adiposity index and LAP levels are very efficient in predicting cardiovascular disease risk factors in various clinical studies (20)(21)(22)(29)(30)(31). In people with T2DM and visceral obesity, lipid and lipoprotein metabolism problems are common, resulting in diabetic dyslipidemia and a high risk of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%